THE SPIN-DOWN TORQUE DECAY WITH THE CHARACTERISTIC AGE FOR BINARY MILLISECOND PULSARS (MSPS) STARS - Abdullah, Sundus (Iraqi Journal of Science, 2024)
Millisecond pulsars (MSPs) type have properties differs from normal pulsars type. In this research the characteristic age are concentrated depends on the periods (P), and period derivative (P`) for a sample stars which adopted. Also the value of characteristic age for these stars is determined by depending on the (Ostriker and Gunn) model. The relation between luminosity and the characteristic age for a sample of MSPs stars are illustrated depending on pulse periods for these stars. The results indicate that the spin down torque must decay with the characteristic age for a sample stars which adopted. Also the results for these stars at distance 1.5 kpc from the galactic disk illustrated that the decay must due to the main energy loss mechanism is magnetic dipole radiation, they attributed this to tendency of rotation axis to align with magnetic axis as pulsar age . It is found that the radio luminosity of pulsars must decrease with age, in a good agreement with previous study.